Corrigendum “Prescription patterns of diclofenac in patients with cardiovascular diseases or at high risk for cardiovascular diseases at primary health care level in Montenegro: Retrospective, national, drug utilization study” - Editorial (Vojnosanitetski Pregled)
In the original article titled “Prescription patterns of diclofenac in patients with cardiovascular diseases or at high risk for cardiovascular diseases at primary health care level in Montenegro: retrospective, national, drug utilization study” published in the September 2023 issue of the Vojnosanitetski Pregled 1, the heading for the third, right-hand column of data in Table 1 should have been given as “Patients with CVD/risk for CVD on diclofenac therapy, n (%)” instead of “Patients with CVD on diclofenac therapy, n (%)”. 1. Stanković M, Turković N, Dobrić S, Rančić N. Prescription patterns of diclofenac in patients with cardiovascular diseases or at high risk for cardiovascular diseases at primary health care level in Montenegro: retrospective, national, drug utilization study. Vojnosanit Pregl 2023; 80(9): 778-88. (DOI: https://doi.org/10.2298/VSP221229021S) Link to the corrected article 10.2298/VSP221229021S